KAJIAN SIFAT KIMIA DAN FISKA TANAH PADA LAHAN BEKAS GALIAN MANGAN DI DESA OELAMI - Tobing, Wilda Lumban; Taus, Jonisius; Bria, Deseriana; Tefa, Azor Yulianus; Kolo, Maria Magdalena (Agroprimatech, 2023)
Manganese is a micro nutrient that plants need in small quantities. Manganese plays an important role as an enzyme activator, including phosphate transfer enzymes and enzymes in the Krebs cycle. The aim of this research was to study the chemical and physical properties of the soil on ex-manganese excavated land in Oelami Village, TTU Regency. This research was carried out in June-September 2022. Analysis of the chemical and physical characteristics of the soil was carried out in the laboratory of the Faculty of Agriculture, University of Timor, and the Laboratory of the Faculty of Agriculture, Nusa Cendana University. This study used a descriptive experimental method which was carried out by survey and continued with laboratory analysis. Soil samples were taken at 5 points based on land use. Based on the results of the analysis of the chemical and physical properties of soil from ex-manganese excavated land, pH was 6.321 (slightly sour), CEC 33.46 me/100g (high), C-organic 0.22% (low), N-total 0.22% (low ), P-total 61.44 mg/100g (high), K-total 71.189 mg/100g (high), Mn-total 19,089 ppm (high), organic matter 0.81% (low), sandy loam soil texture ( sand 81.33%, dust 10.67%, and clay 8.00%), soil water content 8.611% (medium), soil density 1.25 g/cm3 (medium), soil specific gravity 1.47 g/ cm3 (low), and porosity 14.961% (high)